Impact of Local Soil Conditions on Earthquake Sensitivity in Erzincan City - Emre Özşahin; İlker Eroğlu (Doğal Afetler ve Çevre Dergisi)
In recent years, uncontrolled growth of cities as a result of rapid population rise has caused people to go towards inappropriate areas in terms of local soil conditions. At the same time, this situation, which increased the depression-sensitive areas in urban centers compared to the old ones, also caused the earthquakes to acquire the features of urban earthquakes. Thus, earthquake sensitivity studies based on local ground conditions have become a necessity for contemporary cities. Employing GIS (Geographic Information Systems) techniques, the present study aims to analyze the effect of the local soil conditions in Erzincan city on earthquake sensitivity through the frequency ratio method. Local soil conditions in the area where the city was established lead to a strong sense of earthquake effect. The study explores the distribution of earthquake sensitivity based on the local soil conditions in the urban area as well as its possible effects on the population. The results of this study show that Erzincan city, where 95,596 (2015) people live, has high earthquake sensitivity. The most sensitive districts to earthquake are Atatürk, İnönü, Karaağaç, Kızılay, and Yenimahalle. The damage that may result from local soil conditions in a possible instant of earthquake will be less in the areas surrounding the city where earthquake sensitivity is moderate. For this reason, considering the earthquake potential and local soil conditions, the existing risks should be taken into consideration in the construction of new buildings, or sites with a lower earthquake sensitivity should be chosen for construction. Especially, the regulations related to the building should be followed carefully in the construction and control stage and the ground improvement should be done if necessary.